Direct‐Writing of 2D Diodes by Focused Ion Beams. (3rd June 2021) - Liu, Yanran; Qu, Yuanyuan; Liu, Yue; Yin, Hang; Liu, Jinglun; Tan, Yang; Chen, Feng
Abstract: Electronic devices based on 2D materials have exhibited outstanding figures of merit. However, the fabrication of 2D diodes still relies on manual or semi‐automated handling processing. To unleash their commercial potential, the integration of 2D materials into a fully‐automated fabrication line is a critical step. Here, the focused ion‐beam writing as an automated approach to construct lateral diodes on a 2D heterostructure (MoSe2 /G) consisting of graphene and MoSe2 is elucidated. Se‐defects generated by focused ion writing endow the 2D heterostructure with unique electronic properties, which allows for the construction of the barrier at the boundary of the writing and non‐writing region. Benefiting from this feature, the ion‐beam‐written heterostructure is used to realize rectifying and current regulating diodes. Exhibiting comparable performance to traditional diodes, the rectifying diode has a rectification ratio of ≈10 4, while the current regulative diode has a dynamic resistance larger than 4.5 MΩ. Furthermore, to illustrate practical applications of these diodes in digital logic electronics, AND and OR logic gates are directly inscribed on the heterostructure by ion beams. This work demonstrates focused ion‐beam writing as an additional strategy for direct‐writing of 2D diodes on graphene‐based heterostructures. Abstract : Focused ion‐beam writing is presented as an efficient strategy for the direct‐writing of electronic circuits on 2D materials. The focused ion beam generates Se‐defects in the MoSe2 /graphene heterostructure, allowing for the construction of Schottky barriers at the boundary of the writing and non‐writing region. Benefiting from this feature, rectifying diodes are constructed with a rectification ratio of ≈10 4 .